Estimating income responses to tax changes: a dynamic panel data approach - Bertil Holmlund; Martin Söderström (Center for Economic Studies and ifo Institute (CESifo), 2007)
Recent research on the behavioral effects of income taxes has to a large extent focused on the elasticity of taxable income with respect to the net-of-tax rate, i.e., one minus the marginal tax rate. We offer new evidence on this matter by making use of a large panel of Swedish tax payers over the period 1991-2002. Changes in statutory tax rates as well as discretionary changes in tax bracket thresholds provide exogenous variations in tax rates that can be used to identify income responses. We estimate dynamic income models which allow us to distinguish between short-run and long-run effects in a straightforward fashion. The estimates of the long-run elasticity of income with respect to the net-of-tax rate typically hover in a range between 0.20 and 0.30. The short-run elasticities are in general smaller but less precisely estimated. We use the estimates to simulate the fiscal consequences of a tax reform that reduces the top marginal tax rate by five percentage points. Such a reform turns out to have negligible effects on tax revenues and may even yield a fiscal surplus.
Keywords: H24; H31; J22; 330; marginal tax rates; progressive taxes; earned income; tax reform; Steuerreform; Einkommensteuer; Einkommenselastizität; Grenzsteuersatz; Steuerprogression; Schätzung; Schweden